(untitled) (INTERNATIONAL SEMINAR, 2024)
This study aimed to investigate the effect of sleep quality on the mental health of university students, especially with regard to stress and anxiety levels. The results showed that poor sleep quality, especially sleeping less than six hours each night, was significantly associated with increased stress and anxiety. Students who experience sleep disturbances often feel anxious and depressed, which negatively impacts their concentration and academic productivity. Factors such as high academic pressure, the habit of using gadgets before bedtime, as well as unfavourable sleeping environment conditions also affect students’ sleep quality. In contrast, those who slept enough with good sleep quality felt calmer and more able to cope with academic demands without feeling overwhelmed. Based on these findings, it is recommended that university students increase their awareness of the importance of quality sleep and adopt healthier sleep habits. The creation of a comfortable and supportive sleep environment, as well as avoiding bad habits such as using gadgets before bedtime, can contribute to improved sleep quality. Thus, maintaining good sleep quality can help university students reduce anxiety and stress, and support their overall mental well-being, which in turn can improve their academic performance and quality of life.